LEVELS OF PHYSICAL ACTIVITIES BEING PRACTICED BY LIRA UNIVERSITY UNDERGRADUATE WEEKDAY STUDENTS AT LIRA UNIVERSITY, NORTHERN UGANDA. A CROSS-SECTION STUDY. - Okullo Christopher Oneka; Freda Amito Oceng; Modi, Derick; Nakaziba, Rebecca; Dr. Ayella, Paul Stephen Ataro (SJ Insights, 2025)
Background Regular physical activity lowers the risks of many non-communicable diseases (NCDs) which is the primordial prevention of diseases. Therefore, this study aimed to determine the levels of physical activities being practiced by Lira University undergraduate weekday students at Lira University. Methodology A descriptive, cross-sectional study design employing quantitative data collection and analysis techniques was used in this study, stratified sampling technique was used in order to establish a sampling frame from each Faculty after which a probability simple random sampling technique was followed in the selection of the respondents. Data was entered for analysis by SPSS version 20. Results 200 respondents participated in this study; males were (122) 61% more than females who were (78) 39%. More than half of participants 167(83.5%) leaving only 33(16.6%) who do not engage in PA at any level. The average prevalence level of engaging in very low, low, high, and very high levels of PA this study found is 23.73% and 29.82%, 20%, and 21.45% respectively. Participation in light (χ² = 23.39, df = 1, p = 0.000*), moderate (χ² = 10.609, df = 3, p = 0.014*), and heavy physical activities (χ² = 13.37, df = 1, p = 0.000*) all show significant differences. Conclusion The study found that the prevalence of participation in PA is generally at 83.5% but the levels of engagement in PA are categorized as very low, low, high, and very high at 23.73%, 29.82%, 20%, and 21.45% respectively. Recommendations Improving participation in physical activity among Lira University undergraduate weekday students should involve a multifaceted approach that addresses various barriers and motivations.